SAE Technical Paper Series 2007
DOI: 10.4271/2007-01-0472
|View full text |Cite
|
Sign up to set email alerts
|

Particulate and Hydrocarbon Emissions from a Spray Guided Direct Injection Spark Ignition Engine with Oxygenate Fuel Blends

Abstract: The blending of oxygenated compounds with gasoline is projected to increase because oxygenate fuels can be produced renewably, and because their high octane rating allows them to be used in substitution of the aromatic fraction in gasoline. Blending oxygenates with gasoline changes the fuels' properties and can have a profound affect on the distillation curve, both of which are known to affect engine-out emissions. In this work, the effect of blending methanol and ethanol with gasoline on unburned hydrocarbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 23 publications
5
52
1
1
Order By: Relevance
“…Saturation in temperature drop during injection has also been measured optically by Beyrau et al [56]. In an identical engine to that of the current study, the overall effect of saturation was a temperature difference between gasoline and ethanol at the spark-plug location at ignition timing of only ~8 K [51], i.e. well in agreement with what quoted earlier.…”
Section: Characteristics Of Heat Releasesupporting
confidence: 81%
See 1 more Smart Citation
“…Saturation in temperature drop during injection has also been measured optically by Beyrau et al [56]. In an identical engine to that of the current study, the overall effect of saturation was a temperature difference between gasoline and ethanol at the spark-plug location at ignition timing of only ~8 K [51], i.e. well in agreement with what quoted earlier.…”
Section: Characteristics Of Heat Releasesupporting
confidence: 81%
“…Analysis of data from evaporation modelling and wall heat flux measurements with the exact same liquid fuels by [39], and from charge cooling measurements with various oxygenated blends using a cold wire resistance thermometer by [51], indicated that the higher levels of charge cooling during injection with alcohol fuels can result in gradual reduction in the evaporation rate overall because the latter can be limited by fuel saturation due to the higher mass injected and/or by diffusion and mixing. Saturation in temperature drop during injection has also been measured optically by Beyrau et al [56].…”
Section: Characteristics Of Heat Releasementioning
confidence: 99%
“…When the engine is working at the same load, a significant reduction of the PN distribution of the particles can be observed for the ethanol blends equated to gasoline (HE0). The results here are consistent with the PN distribution results reported in previous publications [43][44][45][46][47][48][49]62]. There are many causes leading to a decrease of the PN in the ethanol blends; compared with gasoline fuel, hydrous ethanol and anhydrous ethanol have no aromatic content, a higher laminar flame propagation speed, and a higher percentage of oxygen content.…”
Section: Pm Emission Characteristicssupporting
confidence: 82%
“…Price et al [43] reported that anhydrous ethanol blends E85 and E30 showed the lowest PM emissions, followed by methanol blends M85 and M30 for lean fuel-air mixtures. Another investigation issued by Chen et al [44] detected a reduction of PM emissions when running E10 over gasoline under cold conditions by a coolant temperature of 20 • C. Muralidharan et al [45] noticed that the addition of anhydrous ethanol in gasoline had decreased the particle number in both steady speed and transient conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation